The Alteration Tissue Structure of Digestive diverticulum of Anodonta woodiana Induced by Lead - Putra, Renanda Baghaz Dzulhamdhani Surya; Andayani, Sri; Ningsih, Hartati Kartika; Arfiati, Diana; Hertika, Asus Maizar Suryanto (Graduate School, Universitas Brawijaya, 2018)
Accumulated the toxic compound such as lead in A. woodiana caused an alteration in tissue. The aim of the present study is observation through histology to determine the alteration of the structure of digestive diverticulum tissue. A. woodiana were maintained in water tub that treated lead II nitrate exposure (Pb(NO3)2) 0, 15, 25, 35 mgL-1 for 7 days to determine the alteration of the structure of damaged the digestive diverticulum and determining water quality such temperature, DO and pH. The highest damage occurs in digestive diverticulum treated 35 mgL-1 due to the many alteration tissue structure such as hyperplasia, edema, atrophy, necrosis with the percentage of total damage of about 35%. the lowest alteration tissue structure occurs in 15 mgL-1 treatment group of the digestive diverticulum. the temperature was observed at about 25.3 - 26.4°C, pH about 6-7, and DO about 6.1-6.7 mgL-1. Thus, the increment of lead dose treatment induces increment of tissue structure alteration in digestive diverticula tissue, therefore, might promote the death of Anodonta woodiana. Keywords: Anodonta woodiana, digestive diverticulum, histology